TATA KELOLA PEMBAGIAN PENGHEMATAN DARI HASIL STUDI VALUE ENGINEERING PADA PROYEK INFRASTRUKTUR: ANALISIS PERBANDINGAN SKEMA KONTRAK DAN REGULASI - Alvin Tehmono; Mega Waty; Gede B. Suprayoga (Jurnal Jalan Jembatan, 2026)
This study examines the distribution of cost savings generated from the implementation of Value Engineering (VE) during the construction phase of public infrastructure projects. Although VE has been widely applied to enhance project value by optimising the relationship between function and cost, the institutional arrangement for allocating savings during construction remains ambiguous within Indonesia’s regulatory framework. The research employs a qualitative desk study using descriptive-comparative analysis of international standards and national regulations, including the SAVE International VM Guide (2020), the Fédération Internationale des Ingénieurs-Conseils contract standards (1999 and 2017 editions), and Indonesian regulations (Ministerial Regulation No. 45/2007 and No. 22/2018). The findings indicate an institutional shift from prescriptive gain-sharing mechanisms toward arrangements that depend more on contractual design and fiscal governance. In public infrastructure projects, VE savings are increasingly treated not as direct financial incentives but as instruments for managing fiscal risk within the project lifecycle. The study proposes a hybrid conditional governance model in which VE savings are initially retained as an adaptive contingency buffer to maintain fiscal stability and are distributed only once project uncertainties have been adequately mitigated. These study findings clarify the governance of VE savings and highlight the need to balance innovation incentives with fiscal stability in public project management.   Kata Kunci: Value Engineering, , alokasi penghematan, skema kontrak konstruksi, tata kelola proyek, stabilitas fiskal, studi meja kualitatif Keywords (urutannya harus sama dengan yang Bahasa indonsia untuk kata kunci): value engineering Construction contract schemes, qualitative desk study, fiscal stability, project governance, savings allocation, value engineering.